Logični modeli računalniških struktur - Gerkeš, Maksimiljan (Informatica (Ljubljana), 1985)
The concept of state and operation, as it is known from software design is basic concept with extended interpretation. Collection of compound operations consists of select, sequential and parallel operation. An infinite loop operation with no exit terminal is defined. Compound operations can be changed with a set of defined transformations into a different forms which can be simply modeled with SSI, MSI, LSI, or even VLSI structures, including gate arrays. Models for some characteristic logic and computer structures are proposed on that base.
Keywords: programiranje; programska oprema